ROLE OF ACADEMIC INSTITUTION TO INFORM REGIONAL-SCALE BIODIVERSITY CONSERVATION IN THE EASTERN PHILIPPINES - Jonathan Jaime G Guerrero; Krizler C Tanalgo; Carlo Gabriel R Abante (Journal of Tropical Life Science, 2021)
The Philippines is among the most threatened biodiversity hotspots. Developing effective conservation requires science-based evidence from field data and observations. Yet, many important biodiversity information remain unpublished, particularly from academic institutions and NGOs. Here, we synthesized 34-year data from biodiversity studies from Bicol University in Luzon Island, Philippines. We found a large number of studies that increased in the post-2000 period with the majority of the studies focused on community surveys and animal and wildlife studies. While there is a massive number of studies, we found clear disproportionate distribution in terms of geographic and thematic areas. Our results may be based on a regional level, but if taken carefully, it has important implications and applications to other higher education institutions in the Philippines in promoting biodiversity studies and conservation in the country.